MEMBANGUN KESADARAN KESEHATAN MENTAL PADA REMAJA DAN ORANG TUA - Desi Novitasari; Dina Ridhatul Fatimah; Fitri Amalia Delupango (Journal of Hulonthalo Service Society (JHSS), 2023)
This community service aims to build mental health awareness among adolescents and parents in Timbuolo Village, Botupingge District, Bone Bolango Regency. This activity was carried out on July 10, 2024, targeting people aged 17-65 years. The methods used were health education and interactive discussions designed to provide an in-depth understanding of the importance of mental health. The results of the activity showed a significant increase in community understanding of mental health and a commitment to supporting individuals with mental health problems. This program also identified major barriers to community acceptance of mental health issues and provided practical solutions to overcome them.